Sony vs Toshiba : the fog of a format war obscured a complicated high definition landscape - Elias, Jaan; Nagy, Andrea; Oster, Sharon M.; Rosenthal, Jean W., 1945-; Hutchins, Spencer ([London] : SAGE, 2016)
In August of 2005, Sony and Toshiba suspended talks aimed at creating a unified standard for the next-generation, high definition DVD format. This case examines the issues which marked the differences between the two companies.
Originally Published in: Elias, J., Nagy, A., Oster, S., Rosenthal, J. W., & Hutchins, S. (2006). Sony vs Toshiba: The Fog of a Format War Obscured a Complicated High Definition Landscape. 06-016. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Soni Kabushiki Kaisha; Toshiba, Kabushiki Kaisha; Technological innovations -- Case studies; New products -- Case studies; Strategic alliances (Business) -- Case studies